Metabolic Pathways Involved in Regulatory T Cell Functionality - Kempkes, Rosalie W. M.; Joosten, Irma; Koenen, Hans J. P. M.; He, Xuehui (Frontiers in Immunology, 2019)
Regulatory T cells (Treg) are well-known for their immune regulatory potential and are essential for maintaining immune homeostasis. The rationale of Treg-based immunotherapy for treating autoimmunity and transplant rejection is to tip the immune balance of effector T cell-mediated immune activation and Treg-mediated immune inhibition in favor of Treg cells, either through endogenous Treg expansion strategies or adoptive transfer of ex vivo expanded Treg. Compelling evidence indicates that Treg show properties of phenotypic heterogeneity and instability, which has caused considerable debate in the field regarding their correct use. Consequently, for further optimization of Treg-based immunotherapy, it is vital to further our understanding of Treg proliferative, migratory, and suppressive behavior. It is increasingly appreciated that the functional profile of immune cells is highly dependent on their metabolic state. Although the metabolic profiles of effector T cells are progressively understood, little is known on Treg in this respect. The objective of this review is to outline the current knowledge of human Treg metabolic profiles associated with the regulation of Treg functionality. As such information on human Treg is still limited, where information was lacking, we included insightful findings from mouse studies. To assess the available evidence on metabolic pathways involved in Treg functionality, PubMed, and Embase were searched for articles in English indexed before April 28th, 2019 using “regulatory T lymphocyte,” “cell metabolism,” “cell proliferation,” “migration,” “suppressor function,” and related search terms. Removal of duplicates and search of the references was performed manually. We discerned that while glycolysis fuels the biosynthetic and bioenergetic needs necessary for proliferation and migration of human Treg, suppressive capacity is mainly maintained by oxidative metabolism. Based on the knowledge of metabolic differences between Treg and non-Treg cells, we additionally discuss and propose ways of how human Treg metabolism could be exploited for the betterment of tolerance-inducing therapies.